Blast Furnace Ironmaking: Process Alternatives and Carbon Intensity - P. Chris Pistorius; Jorge Gibson; Megha Jampani (The Minerals, Metals and Materials Society, 2014)
"The main reason for the significant carbon intensity of integrated steelmaking (approximately 1.8 tons of CO2 per ton of steel) is the use of carbon-based reductants in blast furnace ironmaking. Several changes to blast furnace ironmaking have been proposed as ways to reduce carbon intensity and cost. A conceptually simple two-zone blast furnace mass and energy balance can be used to quantify the expected impact of such process changes on coke rate, carbon intensity, and productivity. Examples to be discussed include top gas recycling, combining lower blast temperatures with increased coal injection to produce a rich top gas, using prereduced feed, and tuyère injection of natural gas. The use of the operating window – which illustrates how allowable flame temperatures and top-gas temperatures constrain feasible oxygen enrichment levels – is illustrated. Increased use of natural gas would lower the carbon intensity of blast furnace ironmaking.IntroductionBecause of the significant carbon intensity of steelmaking (approximately 1.8 tons of CO2 emitted per ton of steel produced) and the high production rate of steel (more than 1.4 billion tonnes per annum), steelmaking is responsible for a large percentage, approximately 6.7%, of world anthropogenic CO2 emissions [1]. By far the largest input of the carbon into conventional steelmaking is as coke, which is essential to blast furnace ironmaking. A typical fuel rate for blast furnace ironmaking is 450 kg of fuel per tonne of hot metal (THM). (""Fuel"" includes coke and injectants which partially replace coke; pulverized coal and natural gas are typical injectants.) Assuming the fuels to contain 90% carbon on average, and since nearly all of this carbon exits the steel plant as CO2, a fuel rate of 450 kg is equivalent to a CO2 intensity of 1485 kg/THM – by far the largest part of the total CO2 intensity of steelmaking.Blast furnace ironmaking is expected to remain the main source of new iron units; this paper gives some estimates of the extents to which further reductions in carbon intensity from blast furnace ironmaking is possible. A recent European assessment suggested that blast furnace process intensification options such as increased pulverized-coal injection or natural gas injection would yield only modest energy savings [2]. However, if the focus is on CO2 emissions rather than on total energy use, there would be an advantage to using fuels – such as natural gas – which have lower carbon contents relative to energy content."